Design of tunnel inspection robot for large diameter sewers - Burhan (2018)
The Singapore used water transport infrastructure comprises of three sewage systems: trunk sewer, link sewer network and the Deep Tunnel Sewerage System (DTSS). It is a solution towards Singapore’s long-term water needs such as used water collection, treatment, reclamation and disposal. Environmental conditions and activities in and outside the tunnels can lead to deterioration of tunnel assets such as liner cracking, dislocated joints or even collapsed sections over an extended period. Leaks from sewer tunnels may contaminate the surrounding land and pose risks to public health. In order to prolong the service life of sewers and to protect surrounding environment, inspecting the structural integrity of the tunnel is an essential part of infrastructure maintenance. The use of robots is one of the options being explored to assess underground spaces and to achieve enhanced inspection and maintenance capabilities. This option is desirable as it reduces the risk to humans resulting from prolonged incursions into a hazardous environment. The presence of biological contagions, hazardous and explosive gases (predominantly hydrogen sulphide, methane etc.) can pose a threat to the wellbeing of humans. Oxygen deprivation, absence of illumination and slippery conditions can further add to the risk level. In addition, automation promises greater reliability and manpower savings. Deploying robots into modern-day sewer systems are not without its engineering and technological challenges. Frequently there are restrictions to access through manhole openings. Access tunnels may have further structural obstructions to permit the use of launch support mechanisms. In addition, the depth of service tunnels approaches 50 m with distances between adjacent accesses points approaching 2 km. Keeping the robots supplied with power is challenging and with conflicting operational advantages and disadvantages between on-board battery and surface supplied power. The paper provides insights to the identification of design considerations and field trial for our tunnel inspection robot.